Phantom Eye Syndrome: A Review of the Literature - Agda M. Andreotti; Marcelo C. Goiato; Eduardo P. Pellizzer; Aldiéris A. Pesqueira; Aimée M. Guiotti; Humberto Gennari-Filho; Daniela M. dos Santos (The Scientific World Journal)
The purpose of this literature review was to describe the main features of phantom eye syndrome in relation to their possible causes, symptoms, treatments, and influence of eye amputation on quality of life of anophthalmic patients. For this, a bibliographical research was performed in Pubmed database using the following terms: “eye amputation,” “eye trauma,” “phantom eye syndrome,” “phantom pain,” and “quality of life,” associated or not. Thirteen studies were selected, besides some relevant references contained in the selected manuscripts and other studies hallowed in the literature. Thus, 56 articles were included in this review. The phantom eye syndrome is defined as any sensation reported by the patient with anophthalmia, originated anophthalmic cavity. In phantom eye syndrome, at least one of these three symptoms has to be present: phantom vision, phantom pain, and phantom sensations. This syndrome has a direct influence on the quality of life of the patients, and psychological support is recommended before and after the amputation of the eyeball as well as aid in the treatment of the syndrome. Therefore, it is suggested that, for more effective treatment of phantom eye syndrome, drug therapy should be associated with psychological approach.